INFLUÊNCIA DA FORÇA IÔNICA NO PROCESSO DE ADSORÇÃO DO GLIFOSATO NA BENTONITA DECORADA COM ÍONS EURÓPIO - KOCH, Camila dos Santos Rodrigues Marciano; TRENKEL, Fernanda Adriéli; ARRUDA, Gilberto José (ANAIS DO ENIC, 2025)
-